2018
DOI: 10.2196/mhealth.9854
|View full text |Cite
|
Sign up to set email alerts
|

A Mobile Technology Intervention With Ultraviolet Radiation Dosimeters and Smartphone Apps for Skin Cancer Prevention in Young Adults: Randomized Controlled Trial

Abstract: BackgroundSkin cancer is the most prevalent and most preventable cancer in Australia. Despite Australia’s long-running public health campaigns, young Australian adults continue to report high levels of ultraviolet radiation (UVR) exposure and frequent sunburns. Young people are now increasingly turning away from traditional media, such as newspapers and TV, favoring Web-based streaming, which is challenging the health care sector to develop new ways to reach this group with targeted, personalized health promot… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(50 citation statements)
references
References 28 publications
0
47
0
3
Order By: Relevance
“…Four studies assessed sun‐related attitudes, of which three found significant differences in the sun risk attitude and perceived sun damage susceptibility . Sixteen studies found a significant protective behavioural changes and two studies reported significant changes in the intention to change sun protection behaviour …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Four studies assessed sun‐related attitudes, of which three found significant differences in the sun risk attitude and perceived sun damage susceptibility . Sixteen studies found a significant protective behavioural changes and two studies reported significant changes in the intention to change sun protection behaviour …”
Section: Resultsmentioning
confidence: 99%
“…A powerful tool could be smart phones, which through the use of text messages and Apps could be useful methods for teaching individuals sun‐related knowledge in order to change attitudes and behaviours. Messaging could be individually tailored, which could be beneficial in the sense that they are more effective for health behaviour changes compared to standard messages .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hacker et al [57] performed a prospective study in 2018 comparing the effectiveness of a personal UVR dosimeter and a "SunSmart" mobile application in altering sun protection habits over 3 months. The app displayed the daily UVI, information on interpreting the UVI, the weather forecast, and a vitamin D tracker tool.…”
Section: Resultsmentioning
confidence: 99%
“…Since question 2 is oriented to target electronic means of UVI communication for mobile athletes, we added various restrictions in place of “Behavior” including “Mobile”, “Email”, and “App”, yielding one relevant citation [ 56 ]. Additional focused searches discovered 3 more articles [ 57 59 ]. For questions 3–5, we evaluated studies from January 1990 through December 2018 utilizing the following search criteria in PubMed: ((“skin cancer”/sports) OR “skin cancer” prevalence AND “sports” [MeSH]).…”
Section: Methodsmentioning
confidence: 99%